Orientasi dan Penanaman Jenis Tanaman Kelapa untuk Upakara di Dusun Santi Desa Selat Kecamatan Selat Karangasem - Suwantana, I Gede; Subagia, I Nyoman; Sudiana, I Gusti Ngurah; Surada, I Made; Relin D.E; Adnyana, Putu Eka Sura; Rema, I Nyoman; Tirta, I Made Danu; Giri, I Putu Agus Aryatnaya; Aryana, I Made Putra (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
The functions of coconuts are many. Besides for consumption purposes, coconut is also widely used as a means of ceremonies in Bali. Its use has increased in recent years so its availability also needs to be improved. Especially for upakara coconut is becoming increasingly rare nowadays because growing it is not easy. For example, a giant coconut, in addition to producing little fruit, also needs special care and a special place to grow it—likewise several other types of coconut. Thus, the Postgraduate Doctoral Program at UHN I Gusti Bagus Sugriwa Denpasar took the initiative to carry out study-based service in the form of orientation and planting coconut species for ceremonies in Santi hamlet, Selat village, Selat sub-district, Karangasem. Descriptively this work tries to narrate the service activities along with several types of upakara coconut plants planted there. The community in Santi hamlet itself is very enthusiastic about planting these plants and directly getting the benefits.